AAV genome loss from dystrophic mouse muscles during AAV-U7 snRNA-mediated exon-skipping therapy - Le Hir, M; Goyenvalle, A; Peccate, C; Précigout, G; Davies, K; Voit, T; Garcia, L; Lorain, S (2013)
In the context of future adeno-associated viral (AAV)-based clinical trials for Duchenne myopathy, AAV genome fate in dystrophic muscles is of importance considering the viral capsid immunogenicity that prohibits recurring treatments. We showed that AAV genomes encoding non-therapeutic U7 were lost from mdx dystrophic muscles within 3 weeks after intramuscular injection. In contrast, AAV genomes encoding U7ex23 restoring expression of a slightly shortened dystrophin were maintained endorsing that the arrest of the dystrophic process is crucial for maintaining viral genomes in transduced fibers. Indeed, muscles treated with low doses of AAV-U7ex23, resulting in sub-optimal exon skipping, displayed much lower titers of viral genomes, showing that sub-optimal dystrophin restoration does not prevent AAV genome loss. We also followed therapeutic viral genomes in severe dystrophic dKO mice over time after systemic treatment with scAAV9-U7ex23. Dystrophin restoration decreased significantly between 3 and 12 months in various skeletal muscles, which was correlated with important viral genome loss, except in the heart. Altogether, these data show that the success of future AAV-U7 therapy for Duchenne patients would require optimal doses of AAV-U7 to induce substantial levels of dystrophin to stabilize the treated fibers and maintain the long lasting effect of the treatment. © The American Society of Gene and Cell Therapy.